Code Mixing and Slang as The Effect The Development of Technology in Gameplay - Almira Rahma Syastuti; Damay Rahmawati (LPPM Universitas Duta Bangsa Surakarta, 2021)
This study focuses on analyzing code mixing and slang word as the Effect The Development of Technology in Gameplay. It is chosen because code switching and code mixing is very important for everyone, especially for modern era. Sometimes they need some languages to speak with other people around them. Some of them switch or mix their native language with foreign language or their second language. This research shows that structural elements of code mixing and slang word in gameplay.